Hyperosmolarity Induces Armanni‐Ebstein‐like Renal Tubular Epithelial Swelling and Cytoplasmic Vacuolization. Issue 1 (27th October 2016) - Zhou, Chong; Vink, Robert; Byard, Roger W.
Abstract: Armanni–Ebstein lesions have been considered pathognomonic for diabetes mellitus and appear as markedly swollen renal tubular epithelial cells with cytoplasmic clearing and glycogen accumulation. However, the extent to which hyperosmolarity contributes to the Armanni–Ebstein phenotype is unclear. Ten sheep were injected intravenously with 20% mannitol at 11 mOsm/kg, and subsequent histological evaluation of the kidneys showed variable degrees of osmotic nephrosis and cytoplasmic clearing of renal tubular epithelial cells similar to that seen with Armanni–Ebstein lesions. However, although morphological changes similar to Armanni–Ebstein lesions could be produced, no intracytoplasmic glycogen was demonstrated with periodic Acid–Schiff (PAS) stain. This suggests that while hyperosmolarity may contribute to the development of an Armanni–Ebstein phenotype, glycogen accumulation may result from the more complex metabolic effects of glucose on renal tubular epithelial cells. Thus, when Armanni/Ebstein‐like vacuolizations are seen at autopsy, a confirmatory PAS stain is recommended because of the potential effect of hyperosmolar states.